PENINGKATAN KINERJA PEGAWAI DENGAN KONTRIBUSI LINGKUNGAN KERJA DAN KOMPETENSI PADA DINAS KESEHATAN KOTA BANDAR LAMPUNG - Aprianis AprianisAprianis (Universitas Muhammadiyah Metro Lampung, 2019)
Improving employee performance as optimal as possible is not an easy job, because there are many factors that influence this employee's performance improvement. One of them is employee work competencies carried out by the agency on the implementation of the work of its employees. Besides the competency function, another factor is the work environment. The formulation of the problem is whether there is a contribution to the work environment and work competencies both individually and jointly on the performance of employees at the Bandar Lampung City Health Office.The type of research used in this study is quantative research, with independent variables namely environment (X1) and work competency (X2) while the intended variable is dependent on employee performance (Y). Methods of collecting data based on sources using primary and secondary data. The data collection techniques with library research and field research include: observation, questionnaires, documentation and interviews. Based on the results of research, work environment and communication has a contribution to the performance of employees at the Bandar Lampung City Health Office, this is proven by a hypothesis that states accepting statements of contribution between work environment and competency individually or together on the performance of employees of Bandar Lampung City Health Office . Keywords: Environment, Work Competence and Employee Performance